1
$\begingroup$

I wanted to find the value of the following expression

$$\sum_{r=0}^{20} (-1)^r. \binom {30}{r}. \binom {30}{r+10}$$

The Vandermonde's identity could have been used in this problem but the $(-1)^r$ makes it of no use. Using the binomial expansion and some brute force I got the answer as the coefficient of $x^{20}$ in the expansion $(1-x^2)^{30}$. But I am not able to provide the proof in writing because it was just by brute force and some observation. Can someone please provide a hint.

$\endgroup$
  • $\begingroup$ Mathematica gives the answer immediately: $30045015$. What do you mean "closed form" in this context? $\endgroup$ – David G. Stork Jan 24 '18 at 18:24
  • $\begingroup$ @David G. Stork I want a written mathematical proof for my obtained answer not just the expansion of $\binom {30}{10}$. Also typo fixed. $\endgroup$ – Rohan Shinde Jan 24 '18 at 18:26
  • $\begingroup$ What about writing two terms, one for all the $(-1)^{+1}$ cases, and one for all the $(-1)^{-1}$ cases, use identities, and then subtract the results? Hint: $2095922267925255 - 2095922237880240 = 30045015$ $\endgroup$ – David G. Stork Jan 24 '18 at 18:29
  • $\begingroup$ Hint: consider the coefficient of $x^{20}$ in $(1-x)^{30}(1+x)^{30}$. $\endgroup$ – Greg Martin Jan 24 '18 at 18:30
  • $\begingroup$ @Greg Martin how did you arrive at that result. Because somewhere in my roughwork I saw that coming but now I don't remember how I got that one. $\endgroup$ – Rohan Shinde Jan 24 '18 at 18:35
4
$\begingroup$

It is convenient to use the coefficient of operator $[z^n]$ to denote the coefficient of $z^n$ in a series. This way we can write for instance \begin{align*} [z^k](1+z)^n=\binom{n}{k} \end{align*}

We obtain \begin{align*} \color{blue}{\sum_{r=0}^{20}}&\color{blue}{(-1)^r \binom {30}{r} \binom {30}{r+10}}\\ &=\sum_{r=0}^{20}(-1)^r \binom {30}{30-r} \binom {30}{r+10}\tag{1}\\ &=\sum_{r\geq 0}[z^{30-r}](1-z)^{30}[u^{r+10}](1+u)^{30}\tag{2}\\ &=[z^{30}](1-z)^{30}\sum_{r\geq 0}z^r[u^r]u^{-10}(1+u)^{30}\tag{3}\\ &=[z^{30}](1-z)^{30}z^{-10}(1+z)^{30}\tag{4}\\ &=[z^{40}](1-z^2)^{30}\tag{5}\\ &=[z^{40}]\sum_{k=0}^{30}\binom{30}{k}(-1)^kz^{2k}\\ &\color{blue}{=\binom{30}{20}=30\,045\,015}\tag{6} \end{align*}

Comment:

  • In (1) we use the binomial identity $\binom{p}{q}=\binom{p}{p-q}$.

  • In (2) we apply the coefficient of operator twice. We also set the upper limit to $\infty$ without changing anything since we are adding zeros only.

  • In (3) we use the linearity of the coefficient of operator and we apply the rule $[z^{p-q}]A(z)=[z^p]z^qA(z)$.

  • In (4) we apply the substitution rule of the coefficient of operator with $u=z$
    \begin{align*} A(z)=\sum_{r\geq0} a_r z^r=\sum_{r\geq 0} z^r [u^r]A(u) \end{align*}

  • In (5) we do some simplifications and apply the same rule as we did in (3).

  • In (6) we select the coefficient of $z^{40}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.